Fitness of mCherry Reporter Tick-Borne Encephalitis Virus in Tick Experimental Models - Kevély, Ádám; Prančlová, Veronika; Sláviková, Monika; Haviernik, Jan; Hönig, Václav; Nováková, Eva; Palus, Martin; Růžek, Daniel; Klempa, Boris; Koči, Juraj (Viruses, 2022)
The tick-borne encephalitis virus (TBEV) causes a most important viral life-threatening illness transmitted by ticks. The interactions between the virus and ticks are largely unexplored, indicating a lack of experimental tools and systematic studies. One such tool is recombinant reporter TBEV, offering antibody-free visualization to facilitate studies of transmission and interactions between a tick vector and a virus. In this paper, we utilized a recently developed recombinant TBEV expressing the reporter gene mCherry to study its fitness in various tick-derived in vitro cell cultures and live unfed nymphal Ixodes ricinus ticks. The reporter virus was successfully replicated in tick cell lines and live ticks as confirmed by the plaque assay and the mCherry-specific polymerase chain reaction (PCR). Although a strong mCherry signal determined by fluorescence microscopy was detected in several tick cell lines, the fluorescence of the reporter was not observed in the live ticks, corroborated also by immunoblotting. Our data indicate that the mCherry reporter TBEV might be an excellent tool for studying TBEV-tick interactions using a tick in vitro model. However, physiological attributes of a live tick, likely contributing to the inactivity of the reporter, warrant further development of reporter-tagged viruses to study TBEV in ticks in vivo.
Keywords: Animals; Cell Line; Encephalitis Viruses, Tick-Borne; zvířata; buněčné linie; teoretické modely; klíšťová encefalitida; klíště; Models, Theoretical; polymerázová řetězová reakce; Polymerase Chain Reaction; viry klíšťové encefalitidy; Ixodes; Encephalitis, Tick-Borne